Japan : the basics - Hood, Christopher P. (Christopher Philip), 1971- (New York : Routledge, 2024)
"Japan: The Basics is an engaging introduction to the culture, society, and the global positioning of Japan. Starting by looking at the common stereotypes, clichés, and tropes associated with Japan, this accessible introduction to the country is designed to arm readers with key skills and knowledge for their study of Japan. This new edition covers topics including: - How do we go about studying Japan? - What can be learnt about Japan from looking at its transportation system? - What is the impact of an aging society? - What are the connections between popular culture and wider Japanese society? - How does Japan respond to disasters? - How are core values about identity formed and what are their implications? - How did Japan respond to the COVID-19 pandemic? With exercises, discussion points, and reflective questions throughout, Japan: The Basics is ideal starting point for all those studying Japan"--
List of figures and tables -- Notes on style -- Acknowledgements -- Map of Japan -- Preface: Establishing the basics -- Studying Japan -- Signs of the times -- Visual packaging culture -- Shaped by and shaping nature -- Beliefs and practices -- One for all, all for one -- Nationalism and internationalism -- Transnationalism and isolation -- Appendix one - Emoji -- Index
Includes bibliographical references and index.
AAL
Keywords: Japan; Japan -- Study and teaching